Profil Kejadian Kanker Serviks Di Rumkital Dr Ramelan Periode Januari – Desember 2018 - SASTRA JENDRA HAYUNINGTYAS (HANG TUAH MEDICAL JOURNAL, 2021)
Background: cervical cancer as the highest case in Indonesia in 2013, especially in the regions of East Java and Central Java. For the main cause itself is a persistent infection of the Human Papilloma Virus (HPV). However, there are also many factors that can be a risk such as age, parity, hormonal contraceptive use, and sexual activity. Because of the high incidence of cervical cancer in East Java, the purpose of this study was to determine the profile of cervical cancer events in Rumkital DR Ramelan Surabaya during the period January - December 2018. Method : descriptive study with a qualitative approach carried out at the Rumkital Oncology Clinic DR Ramelan surabaya during May - August 2019. The results showed that the majority of cervical cancer cases occur in women > 51 years old. Women with a history of parity ≥ 3 children have the highest percentage of 60%. The age group for first sexual intercourse has the same incidence both at age ≤ 20 years and > 20 years which is 50%. As many as 60% of women have a history of hormonal contraceptive use longer than 4 years. And the highest history of changing sexual partners occurred in those with only one sexual partner, which was 93.3%. Conclusions women aged > 51 years, have a history of parity ≥ 3 children, have sex at an early age ≤ 20 years, and use hormonal contraception ≥ 4 years, have a high risk of being cervical cancer. Keywords: cervical cancer, age, parity, age at first sexual intercourse, duration of use of hormonal contraception, multiple sexual partners.